IMPROVEMENT OF ENDURANCE IN PREPARING THE BIATHLON SKI TESTS THROUGH MEANS SPECIFIC TO ATHLETICS AT JUNIOR II LEVEL (Fiep Bulletin - online, 2019)
The performances know today a vertiginous growth in all sports branches, firstly determined by thecontinuous perfection of methods and means of physical qualities improvement, their development process regarding thesmallest details, in a unanimous opinion of the specialists.Taking into account the morpho-functional and psychological peculiarities of the age group of 16-18 years (juniors II)to which the theme of the paper refers, we considered that the approach of physical training through means specific to athleticsendurance at a higher level than the current training is always a hot topic in the biathlon skiers' training.The training program I propose in the paper was selected and rationalized following the pedagogical observationactivity on several groups of skiers within the Dinamo Rasnov School Sports Club. It was followed carefully the factors such as the correlation between cardio-vascular parameters and the performance in endurance effort, the effects of endurance training forheart, the cardiac frequency of sportsmen, the effects of endurance trainings for lungs, breathing technique.The purpose of this research is to experimentally determine the level of endurance improvement following theparticipation to a training program used through specific means of athletics adapted to biathlon ski.
Keywords: biathlon ski; athletic means specific; endurance effort; endurance in biathlon ski